Study on the influence of adiponectin genetic variants and adiponectin levels among Indonesian women with polycystic ovary syndrome (Medical Journal of Indonesia, 2012)
Background: Insulin resistance and central adiposity are frequent disorders in PCOS women, which are marked by biological marker dysregulation related to this metabolic abnormalities. Association between adiponectin and insulin resistance has been investigated in many studies, while only a few studies were done in PCOS patients. This study is to determine the association of T45G polymorphisms in Indonesian population with PCOS biological markers and their influence to adiponectin serum. Methods: Fifty-two PCOS patients and 52 normal ovulatory women without hyperandrogenism as control subjects were included. Blood samples were collected between day 3 and 5 of a spontaneous menstrual cycle at 7 to 9 am, after overnight fasting. Serum levels of FSH, LH, testosterone, SHBG, glucose, insulin, lipid profile and adiponectin were measured. Insulin resistance was estimated by HOMA-IR, HOMA- β, and SHBG. T45G gene polymorphisms were determined by PCR after genomic DNA was obtained from peripheral blood of patients and control subjects. Results: There were significant difference between PCOS and control group in term of BMI, LH, testosterone, SHBG, and FAI, but not significant to T45G gene polymorphisms frequency distribution. Adiponectin levels were lower in PCOS patients than control. There was an association between insulin resistance with PCOS. Among PCOS patients, no association between adiponectin LH, testosterone, SHBG, and FAI with T45G gene polymorphisms. T45G gene polymorphisms were more frequent in PCOS with low adiponectin levels compared to those with high adiponectin levels, although not significant statistically. Conclusion: T45G gene polymorphisms has no direct association with PCOS biological markers, but its association with adiponectin needs further study. (Med J Indones. 2012;21:83-91)